2010
DOI: 10.1016/j.amepre.2010.07.017
|View full text |Cite
|
Sign up to set email alerts
|

New Moves—Preventing Weight-Related Problems in Adolescent Girls

Abstract: Background-Weight-related problems are prevalent in adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
305
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(324 citation statements)
references
References 63 publications
6
305
2
7
Order By: Relevance
“…'New Moves' was funded primarily as an obesity prevention programme for sedentary adolescent girls, but was designed to prevent a broader spectrum of weightrelated problems (134) . The primary component of New Moves is an all-girls physical education class, supplemented with activities aimed at improving eating patterns without dieting and self-image.…”
Section: Proposals and Initiatives For The Integrated Prevention Of Omentioning
confidence: 99%
“…'New Moves' was funded primarily as an obesity prevention programme for sedentary adolescent girls, but was designed to prevent a broader spectrum of weightrelated problems (134) . The primary component of New Moves is an all-girls physical education class, supplemented with activities aimed at improving eating patterns without dieting and self-image.…”
Section: Proposals and Initiatives For The Integrated Prevention Of Omentioning
confidence: 99%
“…For example, Neumark-Sztainer and colleagues [8] examined the effectiveness of a physical education program entitled "New Moves" to target health behaviors and body image among adolescent girls at risk of overweight and obesity. Results from this study [8] indicate that after completing the program, girls reported significant improvements in portion control, reductions in sedentary behavior, and increases in their physical activity self-efficacy and self-reported psychological "stage of change" for both dietary and physical activity behaviors. However, no significant changes were found for physical activity behavior or quality of dietary intake in terms of consumption of fruit and vegetables and sugar-sweetened beverages.…”
mentioning
confidence: 99%
“…Over 60 preventive interventions have been evaluated in controlled studies, the vast majority of which were efficacy trials (Stice et al, 2013). Importantly, there have been a number of notable successes from these trials documenting preventive effects on onset of eating disorders-related psychological and behavioral symptoms and/or body image problems (Austin et al, 2007;Neumark-Sztainer et al, 2010;Stice et al, 2013;Wilksch et al, 2014;Yager et al, 2013).…”
Section: Introductionmentioning
confidence: 99%